1998
DOI: 10.1017/s0048577298970342
|View full text |Cite
|
Sign up to set email alerts
|

Movement‐related potentials accompanying unilateral finger movements with special reference to rate of force development

Abstract: The aim of this study was to examine the relationship between force and rate of force development with electroencephalogram correlates. The primary question was whether the different components of movement related potentials (MRPs) were related to specific properties of force output while subjects performed index finger force production tasks. The peak force and rate of force development (e.g., a product of peak force over time-to-peak force) were manipulated, and the effects of these manipulations on componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 37 publications
5
18
1
Order By: Relevance
“…The morphology of MRCP observed in this study (Fig. 4) is similar to those reported in the literature [11,33,35,36].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The morphology of MRCP observed in this study (Fig. 4) is similar to those reported in the literature [11,33,35,36].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies on MRCPs reported that the surface negativity increases approximately 1 s before the imagination onset and the potential rebounds after the imagination onset [11,33,35,36]. The time course of the average MRCP in this study showed similar characteristics.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar relationships have been observed in a variety of other tasks~see, e.g., Brunia & Vingerhoets, 1980;Slobounov, Ray, & Simon, 1998;Sommer et al, 1994!, so this pattern has wide generality. However, the relationship between the CNV and response speed appears to be much more dependent on the specific task used.…”
Section: Discussionsupporting
confidence: 78%
“…The increased N?50 in our study cannot be explained by exerted force level. In addition, the N?50 increases as the rate of force development increases (Slobounov et al 1998). It also increases with the effort to perform the task (Slobounov et al 2004).…”
Section: Timing Errorsmentioning
confidence: 98%